2006
DOI: 10.1051/0004-6361:20065006
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the X-ray emission from Herbig Ae/Be stars

Abstract: Context. Herbig Ae/Be stars are fully radiative and not expected to support dynamo action analogous to their convective lower-mass counterparts, the T Tauri stars. Alternative X-ray production mechanisms, related to stellar winds or star-disk magnetospheres have been proposed, but their X-ray emission has remained a mystery. Aims. A study of Herbig Ae/Be stars' global X-ray properties (such as detection rate, luminosity, temperature, variability), helps to constrain the emission mechanism by comparison to othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
108
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 96 publications
18
108
0
1
Order By: Relevance
“…Warm H 2 gas is reported by Thi et al (2001). Similar to the case of HD 144668, resolved Chandra images show that most of the Xray emission comes from the T Tauri companion, but weak emission is attributed to the Herbig star (Stelzer et al 2006). HD 176386: a magnetic field is definitely present: we measure B z = −119 ± 33 G using the full spectrum and B z = −121 ± 35 G using hydrogen lines.…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldssupporting
confidence: 68%
See 4 more Smart Citations
“…Warm H 2 gas is reported by Thi et al (2001). Similar to the case of HD 144668, resolved Chandra images show that most of the Xray emission comes from the T Tauri companion, but weak emission is attributed to the Herbig star (Stelzer et al 2006). HD 176386: a magnetic field is definitely present: we measure B z = −119 ± 33 G using the full spectrum and B z = −121 ± 35 G using hydrogen lines.…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldssupporting
confidence: 68%
“…Surprisingly, HD 176386 is one of the few Herbig Ae/Be stars confirmed to be X-ray dark (log L X [erg/s] < 28.6). Stelzer et al (2006) showed on basis of Chandra imaging that apparent X-ray detections of this star in previous lower-resolution observations are to be attributed to the companion at 4 separation.…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldsmentioning
confidence: 73%
See 3 more Smart Citations